SAT0632 NEUTROPHIL ACTIVATION IDENTIFIES PATIENTS WITH ACTIVE POLYARTICULAR GOUT – A NOVEL BIOMARKER?. (June 2019) - Vedder, Daisy; Gerritsen, Martijn; Nurmohamed, Michael; Vollenhoven, Ronald van; Lood, Christian
Abstract : Background: Neutrophils are key immune cells participating in host defense through several mechanisms, including the formation of neutrophil extracellular traps (NETs). Although beneficial from a host-pathogen perspective, excessive neutrophil activation has been linked to inflammation and autoimmunity, including systemic lupus erythematosus (SLE) and gout.(1) In gout models, uric acid crystals induce NETosis. Though NETs are known to induce marked inflammation through TLR9- and cGAS-dependent pathways, as well as partake in induction of tissue damage and thrombotic events, the role of NETs in human gout has not been carefully investigated. Objectives: Our objective is to investigate evidence of systemic neutrophil activation, and the clinical utility of neutrophil-derived biomarkers in gout. We hypothesize that uric acid crystals will activate neutrophils to undergo NET formation, with these processes contributing to immune cell activation, and local joint destruction. Methods: Plasma samples from 75 gout patients participating in the 'Reade gout cohort Amsterdam' were compared with 30 healthy controls (HC). Levels of NETs, and NET-derived markers (cell-free DNA and peroxidase activity) were analyzed using a MPO-DNA ELISA, as well as fluorimetry.(2) Levels of calprotectin (S100A8/A9) were analyzed by ELISA. Mitochondrial (mt, COXII), as well as genomic (n, RPLP0) DNA levels were analyzed by qPCR. All of the analyzed markers were compared between gout patients and healthy individuals, and related to markers of inflammation and disease activity. Results: Levels of NETs, as well as other neutrophil biomarkers, were significantly increased in gout patients as compared to healthy subjects (p<0.01, Figure 1A ). In contrast to SLE, gout patients did not have elevated levels of circulating mtDNA (p=0.96), but only nDNA (p=0.006). No associations were found between markers of cell death (cfDNA and NETs) and disease activity. Peroxidase activity correlated with disease activity (RAPID score: r=0.43, p=0.01, RAPID function: r=0.54, p=0.001) and inflammation markers (CRP: r=0.40, p<0.001, and ESR: r=0.43, p<0.001). Involvement of ankle and wrist resulted in significant higher peroxidase levels compared to mono-articular disease (p=0.01, and p=0.03, respectively), suggesting peroxidase activity being a marker of polyarticular gout (Figure 1B ). Calprotectin (S100A8/A9) correlated with the inflammation markers CRP and ESR (r=0.30, p=0.01, and r=0.30, p=0.001, respectively) and morning stiffness, especially in patients with chronic polyarticular gout (r=0.61, p=0.001). Conclusion: To our knowledge, this is the first report demonstrating presence of NETs in the peripheral blood of gout patients. Although markedly elevated, levels of NETs did not associate with markers of disease activity or inflammation, possibly due to the lack of inflammatory mitochondrial DNA within the NETs. Even so, our data demonstrate an important role of neutrophils in gout pathogenesis, with neutrophil activation markers associating with characteristics of active, and more pronounced polyarticular disease. References: [1] Lee KH, Kronbichler A, Park DD, Park Y, Moon H, Kim H, et al. Neutrophil extracellular traps (NETs) in autoimmune diseases: A comprehensive review. Autoimmun Rev. 2017;16(11):1160-73. [2] Lood C, Blanco LP, Purmalek MM, Carmona-Rivera C, De Ravin SS, Smith CK, et al. Neutrophil extracellular traps enriched in oxidized mitochondrial DNA are interferogenic and contribute to lupus-like disease. Nat Med. 2016;22(2):146-53. Disclosure of Interests: Daisy Vedder Speakers bureau: Novartis, Martijn Gerritsen Grant/research support from: Grunenthal has sponsored the Reade Cohort, Michael Nurmohamed Grant/research support from: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Menarini, MSD, Mundipharma, Pfizer, Roche, Sanofi and UCB, Consultant for: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Menarini, MSD, Mundipharma, Pfizer, Roche, Sanofi and UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Menarini, MSD, Mundipharma, Pfizer, Roche, Sanofi and UCB, Ronald van Vollenhoven: None declared, Christian Lood: None declared